Rice Putative Methyltransferase Gene OsPMT16 Is Required for Pistil Development Involving Pectin Modification - Hasegawa, Kazuya; Kamada, Shihomi; Takehara, Shohei; Takeuchi, Haruki; Nakamura, Atsuko; Satoh, Shinobu; Iwai, Hiroaki (Frontiers in Plant Science, 2020)
Pectin synthesis and modification are vital for plant development, although the underlying mechanisms are still not well understood. Furthermore, reports on the function of pectin in the pistil are limited. Herein, we report the functional characterization of the OsPMT16 gene, which encodes a putative pectin methyltransferase (PMT) in rice. The cell walls of rice leaves contain less pectin, and chemical analysis of pectin in the flower organ had not been previously performed. Therefore, in the present study, the amount of pectin in the reproductive tissues of rice was investigated. Of the reproductive tissues, the pistil was especially rich in pectin; thus, we focused on the pistil. OsPMT16 expression was confirmed in the pistil, and effects of pectin methylesterification regulation on the reproductive stage were investigated by studying the phenotype of the T-DNA insertion mutant. The ospmt16 mutant showed significantly reduced fertility. When the flowers were observed, tissue morphogenesis was abnormal in the pistil. Immunofluorescence staining by pectin-specific monoclonal antibodies of the pistil revealed that total pectin and esterified pectin were decreased among ospmt16 mutants. These results indicate that OsPMT16 contributes significantly to pistil development during reproductive growth.